(untitled) (Fiep Bulletin - online, 2012)
This test is back as a proposal to present the application of knowledge from the Human Kinetics, with aview to better understand the significance and ownership of the content inherent in the practice of Martial Arts /Wrestling, as a way of enhancing the quality of professional intervention of Professional Physical Educationespecially in its pedagogical action within the classes of Physical Education. In the first part of the work I presentthe ideas, concepts and rationales that underlie the understanding of the proposal. The second part developedthe idea on the ownership of the application of existing resources within the Martial Arts / Wrestling and itsexploitation as a pedagogical tool in the intervention of Professional Physical Education. In the third and last part, Ipresent as the culmination of establishing relations between theories and suggested the representations of theproposal in depth, as well as reflections regarding their specificities and challenges.